2014
DOI: 10.3233/jad-131436
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Oil Attenuates the Effects of Amyloid-β on Cortical Neurons in vitro

Abstract: Dietary supplementation has been studied as an approach to ameliorating deficits associated with aging and neurodegeneration. We undertook this pilot study to investigate the effects of coconut oil supplementation directly on cortical neurons treated with amyloid-β (Aβ) peptide in vitro. Our results indicate that neuron survival in cultures co-treated with coconut oil and Aβ is rescued compared to cultures exposed only to Aβ. Coconut oil co-treatment also attenuates Aβ-induced mitochondrial alterations. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 23 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…However, very few studies have investigated the therapeutic effects of the MCT ketogenic diet in light of mitochondrial function, although one in vitro study has reported the attenuation of deleterious Aβ-induced effects on cortical neurons treated with coconut oil (containing high levels of MCT), observing increased cell survival and improved mitochondrial structure and size. 75 Whilst the mechanisms of these observed effects remain unknown, there remains a potential for the role of medium chain fatty acids in this context. In particular, decanoic acid, which has the ability to improve mitochondrial function 51,76 may prove beneficial in the amelioration of Aβ-induced mitochondrial damage.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…However, very few studies have investigated the therapeutic effects of the MCT ketogenic diet in light of mitochondrial function, although one in vitro study has reported the attenuation of deleterious Aβ-induced effects on cortical neurons treated with coconut oil (containing high levels of MCT), observing increased cell survival and improved mitochondrial structure and size. 75 Whilst the mechanisms of these observed effects remain unknown, there remains a potential for the role of medium chain fatty acids in this context. In particular, decanoic acid, which has the ability to improve mitochondrial function 51,76 may prove beneficial in the amelioration of Aβ-induced mitochondrial damage.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…There have been many researches on VCO and its potential to salvage neurons from amyloid-induced degeneration, reduce inflammation, and provide ketone bodies for therapeutic effects and increased cognitive function [11,12,13,14]. However, it is proposed that the anti-amyloidogenic and anti-aggregatory properties are to be found in the phenolic compounds of the plant [15,16], which motivated the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Higher ketone values were associated with greater improvement in paragraph recall with MCT treatment relative to placebo across all subjects [66], [67].…”
Section: Slows the Progression Ofmentioning
confidence: 87%